Studies on Indian Agromyzidae (Diptera) - 2. - Sehgal, V. K. (Contributions to Entomology = Beiträge zur Entomologie, 1965)
The observations recorded in this paper are based on material collected by the autho from Chotanagpur plateau of India. Agromyza tephrosiae De Meijere is transferred to the genus Japanagromyza Sasakawa. A new Melanagromyza species bred from leaf mines on Dolichos lablab Linnaeus is also described. Melanagromyza cuscutae Hering and M. centrosematis De Meijere are recorded as new to India. The host plants of the widely reported tropical species M. metallica (Thomson) were discovered to be Ageratum conyzoides Linnaeus and Bidens pilosa Linnaeus (Compositae). Phytomyza atricornis Meigen remains as the most widespread and polyphagous species in India. Nomenclatural Actstephrosiae de Meijere, 1917 (Japanagromyza), comb. n. hitherto Agromyza tephrosiaedolichi Sehgal, 1965 (Melanagromyza), spec. n.